Informação regulação da assistência suplementar à saúde. - Lima, Clóvis Ricardo Montenegro de (2005)
Banca: Gilda Olinto, Geraldo Amadel Lobato Franco, Manoel Gonçalves Rodrigues, Maria Cynesia Medeiros de Barros Torres, Rosali Fernandez de Souza